(untitled) (Research, Society and Development, 2021)
The present paper aims to analyze the implications of COVID-19 pandemic on a food insecurity in Brazil. Was performed an integrative literature review with search of references from Virtual Library of Health in June 2020 with a strategy included the following terms: COVID-19; Food Insecurity; Brazil; Food; Coronavirus Infection. The references of eligible articles related to guiding question of the study with quantitative or/and qualitative approaches performed in Brazil, published in English, Spanish and Portuguese languages, in a period from January 2020 to June 2021 with open access were included to the study. Obtained data have been included: title, author/year, main objective, methodology and conclusions of each study. The results of the study suggest that COVID-19 pandemic has aggravated the situation of food and nutritional insecurity experienced by the Brazilian population, especially by its most vulnerable parts. Moreover, this situation is associated with various factors, such as political instability and resistance in a decision making in the country, accompanied by budget cuts and deconstruction of fundamental policies and programs for the maintenance of the DHAA, food and nutritional security, which precede the pandemic and contribute to the increase in poverty and hunger. Thereby, although larger studies are needed to better assess the implications of the COVID-19 pandemic on the population’s food insecurity, however, it is essential to strengthen policies, programs and actions that act directly with the aim of promoting the population’s food security.